The Utility of Harvest Recoveries of Marked Individuals to Assess Polar Bear (Ursus maritimus) Survival - Peacock, Elizabeth; Laake, Jeff; Laidre, Kristin L.; Born, Erik W.; Atkinson, Stephen N. (ARCTIC, 2012)
Management of polar bear (Ursus maritimus) populations requires the periodic assessment of life history metrics such as survival rate. This information is frequently obtained during short-term capture and marking efforts (e.g., over the course of three years) that result in hundreds of marked bears remaining in the population after active marking is finished. Using 10 additional years of harvest recovery subsequent to a period of active marking, we provide updated estimates of annual survival for polar bears in the Baffin Bay population of Greenland and Canada. Our analysis suggests a decline in survival of polar bears since the period of active marking that ended in 1997; some of the decline in survival can likely be attributed to a decline in springtime ice concentration over the continental shelf of Baffin Island. The variance around the survival estimates is comparatively high because of the declining number of marks available; therefore, results must be interpreted with caution. The variance of the estimates of survival increased most substantially in the sixth year post-marking. When survival estimates calculated with recovery-only and recapture-recovery data sets from the period of active marking were compared, survival rates were indistinguishable. However, for the period when fewer marks were available, survival estimates were lower using the recovery-only data set, which indicates that part of the decline we detected for 2003 – 09 may be due to using only harvest recovery data. Nevertheless, the decline in the estimates of survival is consistent with population projections derived from harvest numbers and earlier vital rates, as well as with an observed decline in the extent of sea ice habitat. La gestion des populations d’ours polaires (Ursus maritimus) nécessite l’évaluation périodique des mesures du cycle biologique, tel que le taux de survie. Cette information est souvent obtenue dans le cadre des efforts de capture et de marquage à court terme (par exemple, sur une période de trois ans) qui se ...